2018
DOI: 10.22146/ijc.26740
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Edible Films Made from Modified Sweet Potato Starch through Heat Moisture Treatment

Abstract: The edible films were prepared from native sweet potato starch (SPS) or modified sweet potato starch through heat-moisture treatment (HMT). The treatments which were carried out in this research were the different durations of HMT (1, 2, and 3 h) and the SPS concentrations (1, 1.25 and 1.5%). The edible films were characterized by moisture content, thickness, tensile strength, elongation, water vapor permeability (WVP), solubility, morphology, thermal, and x-ray diffraction. The result showed that the thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 26 publications
2
8
0
1
Order By: Relevance
“…The enhanced interactions between polymer chains, which have an impact on the crystallinity and flexibility of the film, may be the cause of this improvement in TS and EAB. The results are also in conformity with previously reported work in which modified sweet potato starch films improved the TS and flexibility of the films (Indrianti et al, 2018). Similar trends were also observed in some previous studies (Chu et al, 2022; Zavareze et al, 2012).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The enhanced interactions between polymer chains, which have an impact on the crystallinity and flexibility of the film, may be the cause of this improvement in TS and EAB. The results are also in conformity with previously reported work in which modified sweet potato starch films improved the TS and flexibility of the films (Indrianti et al, 2018). Similar trends were also observed in some previous studies (Chu et al, 2022; Zavareze et al, 2012).…”
Section: Resultssupporting
confidence: 93%
“…In a previous study, the authors reported that starch concentration has a substantial impact on the film's thickness (Zavareze et al, 2012). Another study reported that the thickness of the film increased drastically with the increase in total solids in the solution in proportion to the starch content (Indrianti et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A similar finding was also found for potato and amaranth starch films [62,73]. Interestingly, a decrease in WVP is observed in some other studies on sweet potato and green plantain banana starch films [74,79].…”
Section: Starch Modification Effect On Edible Film Propertiessupporting
confidence: 87%
“…[5] Potato starch (PS) is considered the most promising carbohydrate for food packaging applications. [6][7][8] Its starch granules are relatively large (25-100 μm), occurring in B-type crystalline structures. [9] The potato starch comprises about 80% large macromolecules of amylopectin and 20% high-molecular-weight amylose, along with a higher extent of covalent phosphate bonds.…”
Section: Introductionmentioning
confidence: 99%